Effect of Stocking Density on Growth Performance, Feather Quality, Carcass Traits, and Muscle Chemical Component of Geese from 49 to 70 Days of Age. (24th September 2019) - Wang, C; Liu, Z L; Xue, J J; Wang, Y M; Huang, X F; Wang, Q G
SUMMARY: An excessively high-stocking density can adversely influence performance, health, and welfare of geese. The optimum-stocking density also should be changed with the increase of age and weight in geese. However, the corresponding density parameter is lacking in different feeding phase. The experiment was conducted to investigate the effect of stocking density on geese from 49 to 70 d of age. Three hundred and sixty 49-d-old female Sichuan white geese were randomly allotted to 6 stocking treatments with 6 replicate pens, stocking densities in each group were 2.5, 3.5, 4.5, 5.5, 6.5, and 7.5 birds/m 2 . Average daily gain (ADG) was reduced as stocking density increased ( P < 0.05), and feed gain ratio (F/G) increased as stocking density increased ( P < 0.05). High-stocking density significantly decreased feather cleanliness of geese ( P < 0.05). Stocking density did not influence slaughter yield, breast meat, leg meat, subcutaneous fat and skin, and abdominal fat yields at 70 d ( P > 0.05). High-stocking density tended to linearly decrease intramuscular fat content of breast meat ( P < 0.05), while stocking density did not influence the content of crude protein and amino acids in breast meat ( P > 0.05). Based on broken-line linear regression analysis, the stocking density of female Sichuan white geese from 49 to 70 d of age was 3.5 and 3.6 birds/m 2 for ADG and F/G, respectively.